Respostas

2014-05-15T22:29:30-03:00
2x+4-8x = 3x-4
2x-8x + 4 = 3x - 4
-6x + 4 = 3x - 4
-6x - 3x = - 4 - 4
- 9x = - 8
x = -8/-9
x = + 8/9



2. (x-10) +3 =2.(x-3)
2x - 20 + 3 = 2x - 6
2x - 17 = 2x - 6
2x - 2x = -6 + 17
    0x = 11
     x = 11/0   = Ф



4.(x-3) +8-10= 3x -4
4x - 12 + 8 - 10 = 3x - 4
4x - 22 + 8 = 3x - 4
4x - 14 = 3x - 4
4x - 3x = - 4 + 14
x = 10


m) 8x-3+8-4x=4.(3x-1)

    8x - 3 + 8 - 4x = 12x - 4
    8x - 4x + 5 = 12x - 4
     4x + 5 = 12x - 4
     4x - 12x = - 4 - 5
         - 8x = - 9
           x = -9/-8
           x = + 9/8